Towards a Framework for Continuous Software Engineering - Barcellos, Monalessa Perini (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
Characteristics and demands of the modern and digital society have transformed the software development scenario and presented new challenges to software developers and engineers, such as the need for faster deliveries, frequent changes in requirements, lower tolerance to failures and the need to adapt to contemporary business models. The adoption of agile practices has allowed organizations to shorten development cycles and increase customer collaboration. However, this has not been enough. Continuous actions of planning, construction, operation, deployment and evaluation are necessary to produce products that meet customers' needs and behaviors, to make well-informed decisions and identify business opportunities. Thus, organizations should evolve from traditional to continuous and data-driven development in a continuous software engineering approach. Continuous Software Engineering (CSE) consists of a set of practices and tools that support a holistic view of software development with the purpose of making it faster, iterative, integrated, continuous and aligned with business. It is a recent topic of Software Engineering, thus there are many open questions. This paper introduces a CSE framework that represents CSE processes, points out some research questions and discusses proposals to address them.